Аdrenal tumors: management tactics - L. Yu. Morgunov (Лечащий Врач, 2021)
Detection of adrenal neoplasms frequency is increasing constantly, their estimated at 1 to10%. Although in each case it is necessary to identify hormonal activity and malignant potential, most of them are represented by hormone inactive and benign adenomas. Approximately a fifth of the adrenal formations after further verification are hormone-active or carcinomas that require surgical treatment. The main goal of imaging studies in adrenal incidentalomas is the timely detection of malignant tumors; to determine the characteristics of neoplasms, computed tomography, magnetic resonance imaging and, if necessary, a number of radioisotope studies are used. The size of the lesion detected on computed tomograms exceeding 4-6 cm, its uneven edge or heterogeneity of the structure, an attenuation coefficient of 10 Hounsfield units or higher with a non-contrast study, washout of the contrast agent after 10 or 15 minutes by less than 40%, calcification and invasion in the surrounding tissues suggest the malignancy of the adrenal gland lesion, the likelihood of this increases with a combination of these signs. The developed visualization methods and laboratory evaluation allow to assess their morphological structure and functionality with high confidence. The principles of monitoring the growth and hormonal activity of adrenal formations had been currently developed, but the aspects of the long-term dynamic monitoring remain poorly understood.